Bioremediation of oil sludge contaminated soil by landfarming with added cotton stalks. (January 2016) - Wang, Shijie; Wang, Xiang; Zhang, Chao; Li, Fasheng; Guo, Guanlin
Abstract: A field bioremediation of oil sludge contaminated soil was conducted by landfarming treatment with added cotton stalks in the Shengli oil field. The ability of landfarming treatment was evaluated to reduce petroleum hydrocarbons and restore soil quality. For 39-month landfarming, the initial concentration of total petroleum hydrocarbons (TPH) was 12.57 mg g −1 for oil sludge contaminated soil. The removal efficiency of TPH, saturated fraction and aromatic fraction was 68.48%, 90.04% and 85.55%, respectively. Degradation of TPH followed first order exponential decay kinetics. Soil physic-chemical properties of soil pH, saline alkali degree, nutrients, organic matters and hydrocarbon degraders were greatly improved. The results of Biolog and PCR-DGGE analysis revealed the improvement of soil microbial quantity and diversity, and the isolated predominant 23 strains showed a shift in soil community structure toward the hydrocarbon degrading species including Streptococcus sp., Shewanella sp., Bacillus sp., Pseudomonas sp., Marinobactera sp., Thermoanaerobacter sp., etc. Highlights: Cotton stalks enhanced landfarming effectiveness of oil-sludge contaminated soil. Landfarming improved soil properties of salinity, nutrients, organic matters, etc. Soil residual TPH decreased with time and fitted a first order exponential kinetic. Soil microbial quantity and diversity increased after 39-month landfarming.